Fatty acid metabolism and the oxidative stress response support bacterial predation - Rikesh Jain; Nguyen-Hung Le; Lionel Bertaux; Jean Baudry; Jérôme Bibette; Yann Denis; Bianca H. Habermann; Tâm Mignot (Proceedings of the National Academy of Sciences, 2025)
Despite growing awareness of their importance in soil ecology, the genetic and physiological traits of bacterial predators are still relatively poorly understood. In the course of a Myxococcus xanthus predator evolution experiment, we identified a class of genotypes leading to enhanced predation against diverse species. RNA-seq analysis demonstrated that this phenotype is linked to the constitutive activation of a predation-specific program. Functional analysis of the mutations accumulated across the evolutionary time in a two-component system and Acyl-CoA-manipulating enzymes revealed the critical roles of fatty acid metabolism and antioxidant gene induction. The former likely adapts the predator to metabolites derived from the prey while the latter protects predatory cells from reactive oxygen species generated by prey cells under stress and released upon lysis during predation. These findings reveal interesting parallels between bacterial predator–prey dynamics and pathogen–host cell interactions.